1903 Or. Special Laws 31, An Act to Incorporate the City of Portland, ch. 3,§ art. 4, § 73, pt.§36. - (:unkn) unknown (My University, 1903)
To regulate or prevent the storage, manufacture, and sale of dangerous, explosive, or combustible materials, including gunpowder, dynamite, giant powder, calcium carbide, nitro-glycerine, oil, and gas, and to provide for the inspection of the same; to prevent, by all proper means, all risks of injury or damage by fire arising from negligence, or otherwise[.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER